Real-world Research of Trastuzumab and Pertuzumab Combined with Chemotherapy in Neoadjuvant Treatment of HER2-positive Breast Cancer - MA Xiangmin; ZHANG Xiangmei; ZHOU Xinping; REN Xiaofei; ZHANG Weifang; LIU Yunjiang (Zhongliu Fangzhi Yanjiu, 2022)
Objective To analyze the efficacy and safety of trastuzumab (H) and pertuzumab (P) combined with different chemotherapy regiments in neoadjuvant therapy for HER2-positive breast cancer. Methods We retrospectively analyzed the clinical data of the patients with HER2-positive breast cancer who received HP combined with chemotherapy as neoadjuvant therapy and completed surgery. The primary endpoint was total pathologic complete response (tpCR) (ypT0/isypN0), the secondary endpoints were breast pathologic complete response(bpCR) (ypT0/is) and axillary pathologic complete response (apCR) (ypN0), and the factors influencing pCR were analyzed. Results A total of 63 patients were included, of whom 23 were treated with TCbHP, 27 were treated with THP regimen, and 13 were treated with AC-THP. The overall tpCR rate was 65.1%, of which TCbHP was 73.9%, THP was 55.6%, and AC-THP was 69.2%. The tpCR rate of HR-negative patients was 79.2%, higher than that of HR-positive 56.4%. The overall bpCR rate was 69.8%, and apCR rate was 81.0%. Univariate analysis showed that HER2 status was a related factor affecting tpCR (P=0.023). The total effective rate by MRI was 87.3%. The level 3 and 4 toxicity of the TCbHP regimen was slightly higher than those of the THP and the AC-THP regimens. Conclusion HP combined with chemotherapy have achieved relatively high pCR. HER2 status is a related factor that affects tpCR. The adverse reactions are controllable.